(untitled) (Scientific journal of the Fergana State University, 2023)
The elemental composition of cherry leaves, fruits, stems and seeds was studied by inductively coupled plasma mass spectrometry. In the studied plant samples, the amount of 43 macro- and microelements was determined. Elements were determined in the amount of 24908.25 mg/l in leaves, 18145.57 mg/l in stems, 16277.86 mg/l in stones and 13365.99 mg/l in fruits. Leaves, seeds and fruits of cherries contain the highest amount of calcium, and stems - potassium. The total amount of macronutrients decreases in the following order: in leaves 23125.221 mg/l, in stems 17192.303 mg/l, in seeds 15037.554 mg/l, in fruits 12810.727 mg/l. The amount of macronutrients in the seeds was 92.84%, in the fruits 94.75%, in the leaves 92.38% and in the stems 95.84%. Among the trace elements, such elements as Fe, Si, Al, Sr, Mn, B, Ti, Zn and Cu have a greater number. The amount of iron in the studied samples was much higher and ranged from 347.638 mg/l to 1018.509 mg/l. Among the toxic elements, Pb, Hg, Cd and As were identified, among which lead has a relatively high concentration. The amount of lead in leaves and stones is higher than in stems and fruits.